Analisis Implementasi Teori Ki Hajar Dewantara: Mengungkap Praktik-Praktik Pendidikan Inovatif Di Sekolah Dasar - Fida Yanti, Wiwin; Hendratno, Hendratno; Istiq'faroh, Nurul (CV. Kurnia Grup, 2023)
The aim of this research is to analyze the application of Ki Hajar Dewantara's theory in learning in elementary schools. Ki Hajar Dewantara is an Indonesian education figure who has an innovative view of the learning process. This article examines innovative educational practices contained in Ki Hajar Dewantara's theory in the elementary school environment. The research methods used include interviews with teachers and school principals, as well as analysis of documents related to curriculum and teaching methods. The collected data was analyzed using a qualitative approach to understand the context and essence of educational practice. The results of this research show that Ki Hajar Dewantara's theories have a positive impact in increasing learning innovation in elementary schools. Innovative educational practices such as character development, holistic approaches, and student empowerment are seen to be realized in the implementation of this theory. This research contributes to enriching understanding of the application of Ki Hajar Dewantara's theory in the context of basic education. The implications of these findings can be the basis for improving education policies and developing teachers to more effectively implement innovative approaches in the learning process.